Redshift-space clustering of SDSS galaxies – luminosity dependence, halo occupation distribution, and velocity bias. Issue 4 (16th September 2015) - Guo, Hong; Zheng, Zheng; Zehavi, Idit; Behroozi, Peter S.; Chuang, Chia-Hsun; Comparat, Johan; Favole, Ginevra; Gottloeber, Stefan; Klypin, Anatoly; Prada, Francisco; Weinberg, David H.; Yepes, Gustavo
Abstract: We present the measurements and modelling of the small-to-intermediate scale (∼0.1–25  h −1  Mpc) projected and three-dimensional redshift-space two-point correlation functions (2PCFs) of local galaxies in the Sloan Digital Sky Survey Data Release 7. We find a clear dependence of galaxy clustering on luminosity in both projected and redshift spaces, generally being stronger for more luminous samples. The measurements are successfully interpreted within the halo occupation distribution (HOD) framework with central and satellite velocity bias parameters to describe galaxy kinematics inside haloes and to model redshift-space distortion effects. In agreement with previous studies, we find that more luminous galaxies reside in more massive haloes. Including the redshift-space 2PCFs helps tighten the HOD constraints. Moreover, we find that luminous central galaxies are not at rest at the halo centres, with the velocity dispersion about 30 per cent that of the dark matter. Such a relative motion may reflect the consequence of galaxy and halo mergers, and we find that central galaxies in lower mass haloes tend to be more relaxed with respect to their host haloes. The motion of satellite galaxies in luminous samples is consistent with their following that of the dark matter. For faint samples, satellites tends to have slower motion, with velocity dispersion inside haloes about 85 per cent that of the dark matter. We discuss possible applications of the velocity bias constraints on studying galaxy evolution and cosmology. In the appendix, we characterize the distribution of galaxy redshift measurement errors, which is well described by a Gaussian-convolved double exponential distribution.